Postoperative adjuvant tyrosine kinase inhibitors combined with anti-PD-1 antibodies improves surgical outcomes for hepatocellular carcinoma with high-risk recurrent factors - Li, Jian; Wang, Wen-qiang; Zhu, Rong-hua; Lv, Xing; Wang, Jin-lin; Liang, Bin-yong; Zhang, Er-lei; Huang, Zhi-yong (Frontiers in Immunology, 2023)
Background: The clinical value of postoperative adjuvant therapy (PAT) for hepatocellular carcinoma (HCC) remains unclear. This study aimed to explore the effect of PAT with tyrosine kinase inhibitors (TKIs) and anti-PD-1 antibodies on the surgical outcomes of HCC patients with high-risk recurrent factors (HRRFs). Methods: HCC patients who underwent radical hepatectomy at Tongji Hospital between January 2019 and December 2021 were retrospectively enrolled, and those with HRRFs were divided into PAT group and non-PAT group. Recurrence-free survival (RFS) and overall survival (OS) were compared between the two groups after propensity score matching (PSM). Prognostic factors associated with RFS and OS were determined by Cox regression analysis, and subgroup analysis was also conducted. Results: A total of 250 HCC patients were enrolled, and 47 pairs of patients with HRRFs in the PAT and non-PAT groups were matched through PSM. After PSM, the 1- and 2-year RFS rates in the two groups were 82.1% vs. 40.0% (P < 0.001) and 54.2% vs. 25.1% (P = 0.012), respectively. The corresponding 1- and 2-year OS rates were 95.4% vs. 69.8% (P = 0.001) and 84.3% vs. 55.5% (P = 0.014), respectively. Multivariable analyses indicated that PAT was an independent factor related to improving RFS and OS. Subgroup analysis demonstrated that HCC patients with tumor diameter > 5 cm, satellite nodules, or vascular invasion could significantly benefit from PAT in RFS and OS. Common grade 1-3 toxicities, such as pruritus (44.7%), hypertension (42.6%), dermatitis (34.0%), and proteinuria (31.9%) were observed, and no grade 4/5 toxicities or serious adverse events occurred in patients receiving PAT. Conclusions: PAT with TKIs and anti-PD-1 antibodies could improve surgical outcomes for HCC patients with HRRFs.